2019
DOI: 10.1590/1806-9282.65.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and hematological factors associated with the progression of Alzheimer's disease: a cohort study

Abstract: SUMMARY OBJECTIVE: We studied the users of the Specialized Drug Distribution Program of the public health network. METHODS: A prospective cohort examined the elderly at two intervals of three years and included 30 patients in phase I and 16 in phase II. The methodology was composed of home visits, anthropometric, nutritional and hematological evaluation. For the progression of AD, the Clinical Dementia Rating (CDR) scale was used. RESULTS: According to the CDR, the disease evolved, since in 2014 most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
1
0
5
Order By: Relevance
“…Previous studies have reported the association between high BMI and the risk of dementia. ( Arnoldussen et al , 2019 ; Bianchi et al , 2019 ; Gregorio et al , 2019 ; Nam et al , 2019 ). A new systematic review study indicates the essential role of nutrition in the pathogenesis and evolution of neurodegenerative diseases ( Bianchi et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the association between high BMI and the risk of dementia. ( Arnoldussen et al , 2019 ; Bianchi et al , 2019 ; Gregorio et al , 2019 ; Nam et al , 2019 ). A new systematic review study indicates the essential role of nutrition in the pathogenesis and evolution of neurodegenerative diseases ( Bianchi et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…tálamo, e induziu inflamação em áreas formadoras de placa. A ingestão de vitamina B3 da dieta está inversamente associada à DA, tendo um efeito protetor no desenvolvimento da doença e no declínio cognitivo (GREGORIO et al, 2019).…”
Section: Relação Entre Hipertensão Arterial E Alzheimerunclassified
“…Estudos relatam que pacientes com DA apresentam deficiências nutricionais de muitas vitaminas e minerais. As deficiências de micronutrientes podem resultar não apenas na perda de massa magra, declínio das funções imunológicas e aumento do risco de fraturas, mas também no dano oxidativo no cérebro e deficiências nos neurotransmissores, prejudicando a função cognitiva (GREGORIO et al, 2019).…”
Section: Relação Entre Hipertensão Arterial E Alzheimerunclassified
See 1 more Smart Citation
“…(MEDEIROS et al, 2016). apenas na perda de massa magra, declínio das funções imunológicas e aumento do risco de fraturas, mas também no dano oxidativo no cérebro e deficiências nos neurotransmissores, prejudicando a função cognitiva (GREGORIO et al, 2019).…”
Section: Nutrição E Alzheimerunclassified